Patterns of Sacred Spaces in the Settlement with Religious Plurality: Balun Village, Lamongan - Agus Subaqin; Antariksa Antariksa; Lisa Dwi Wulandari; Herry Santoso (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
Plurality in religion is one of the absolute realities of social reality that is inevitable. Religious plurality is a challenge to create harmony in the religious life and, on the other hand, a vulnerable source of conflict and disputes by various parties. This study explores the pattern of religious space structure in religious plurality settlements in Balun village, Lamongan Regency. Using a structuralist approach (Levi-Strauss) to structure religious activities in a (1) pragmatic (contextual/technical), (2) syntactic (pattern/layout), and (3) semantic (perception) about space, form and sign to explore the pattern of sacred space with the aspects studied, namely the structure, territory and spatial dynamics of various worship activities in religious plurality settlements on a micro, meso and macro scale. Data was collected through direct observation and in-depth interviews with systematic purposive sampling. The results showed that the pattern of spatial order of religious spaces was formed by utilizing public spaces for religious activities; the change of public space into a space of religious activity forms the flexibility of the functioning of space and changes in the territorial boundaries of sacred space – profane. This research contributes to the theoretical development of spatial patterns of religious spaces in religious plurality settlements and creates a space for tolerance in religious life in Balun village, Lamongan.